Big deal : A repertoire planner of Finnish big band music; 47 compositions from 14 composers - UMO (orkesteri) (Finnish Music Information Centre, 1996)
7 kappaletta.
Keywords: UMO : albumit; 1990-luku; big bandit; jazz; Suomi